The State, Business, and Industrial Change in Canada - McDowaIl, Duncan (Labour / Le Travail, 1991)
The article reviews the book, "The State, Business and Industrial Change in Canada," by Michael M. Atkinson and William D. Coleman.
Keywords: ATKINSON; Michael M.; BOOKS – Reviews; COLEMAN; William D.; INDUSTRIAL management; Nonfiction; STATE; Business & Industrial Change in Canada; The (Book)